Factors Affecting Return to Work Readiness: A Study on Chronic Disease Patients and Business Owners in Indonesia 2022 - Shintia Yunita Arini; Putri Ayuni Alayyannur; Indriati Paskarini; Astriani Dwi Aryaningtyas; Khaulah Nabilah; Devy Syanindita Roshida (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The return to work of all workers suffering from occupational diseases and work-related injuries is regulated by the Indonesian government. This does not apply to employees with nonwork-related chronic illnesses. Workers with chronic illnesses often encounter many obstacles when returning to work, greatly affecting their intention to return to work. Therefore, this study aimed to determine the factors that could affect work readiness among patients with chronic diseases and business owners. Methods: This was a cross-sectional study. The study population included all patients with chronic disease in Indonesia. The research sample used a simple random sampling technique, comprising 332 people. Data were analyzed using ordinal logistic regression tests. Results: There was an effect of 17.1% between age, gender, marital status, years of service, and employment status on the return to work readiness of patients with chronic diseases. The type of company and the presence of employees with chronic diseases in the company can affect the return to work readiness of business owners by 25.4%. Conclusion: Based on this finding, special support from different sectors such as governments, non-governmental organizations, and awareness raising by businesses for people with chronic diseases is needed so that they can return to work. It's ready.